2012
DOI: 10.1016/j.krcp.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tacrolimus according to body composition in recipients of kidney transplants

Abstract: BackgroundCurrently, the dosage of tacrolimus used after transplantation is based on the patient's body weight. However, there is a low correlation between body weight and body composition in kidney transplant recipients. In this study, we evaluate the pharmacokinetics of tacrolimus according to body composition in 18 Korean kidney transplant recipients with stable graft function.MethodsBody composition parameters were calculated using bioelectrical impedance analysis. Pharmacokinetic profiles were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…BMI, which generally increases with age, was shown to be independently related to increased Tc first level, when its value exceeded 24.6 kg/m 2 . It is probably partly due to the altered body fat mass in those patients, as it was shown that Tc dose monitoring based on bioimpedance-derived body composition may provide more adequate dosage that based on BMI [ 19 ]. Of note, in our study, the highest frequency of subjects with first supratherapeutic Tc blood level was observed in the subgroup where both age and BMI exceeded the cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…BMI, which generally increases with age, was shown to be independently related to increased Tc first level, when its value exceeded 24.6 kg/m 2 . It is probably partly due to the altered body fat mass in those patients, as it was shown that Tc dose monitoring based on bioimpedance-derived body composition may provide more adequate dosage that based on BMI [ 19 ]. Of note, in our study, the highest frequency of subjects with first supratherapeutic Tc blood level was observed in the subgroup where both age and BMI exceeded the cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…for those with end‐stage liver disease due to ascites and sarcopenia). Han et al . reported in their kidney transplant study there were no statistical differences in pharmacokinetic profiles between groups with different BMI.…”
Section: Discussionmentioning
confidence: 81%
“…for those with end-stage liver disease due to ascites and sarcopenia). Han et al 18 reported in their kidney transplant study there were no statistical differences in pharmacokinetic profiles between groups with different BMI. However, significant difference in pharmacokinetics was observed between groups once specific body composition values estimated by bioelectrical impedance analysis (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Powodem występujących różnic mogą być takie czynniki jak: wiek, płeć pacjenta, oraz skład masy ciała, głównie procentowa zawartość tkanki tłuszczowej. Doniesienia naukowe z ostatniego okresu sugerują, że w przypadku dobierania odpowiedniego dawkowania terapeutycznego leków immunosupresyjnych powinno się brać pod uwagę, poza masą ciała pacjenta, również zawartość tkanki mięśniowej oraz tłuszczowej [22]. Współistnienie innych schorzeń, narząd przeszczepiony (nerka, wątroba, serce, płuca) oraz czas, jaki upłyną od zabiegu również w znaczącym stopniu wpływają na przyswajanie leku.…”
Section: Faza Przedanalityczna Terapeutycznego Monitorowania Lekówunclassified